Nasopharyngeal cancer: Incidence and prognosis of human papillomavirus and Epstein–Barr virus association at a single North American institution. Issue 4 (18th January 2022) - Wu, Shannon S.; Chen, Bonnie; Fleming, Christopher W.; Shah, Akeesha A.; Griffith, Christopher C.; Domb, Chaim; Reddy, Chandana A.; Campbell, Shauna R.; Woody, Neil M.; Lamarre, Eric D.; Lorenz, Robert R.; Prendes, Brandon L.; et al.
Abstract: Background: The prognostication of Epstein–Barr virus (EBV) and human papillomavirus (HPV) status in nasopharyngeal cancer (NPC) is unclear. Methods: This retrospective study analyzed NPC from 2000 to 2019. Results: Seventy‐eight patients were included: 43 EBV +, 12 HPV +, 23 EBV − /HPV −, and 0 EBV + /HPV + . All p16 + tumors were also positive for HPV‐CISH. Baseline characteristics were not different between groups except age, N‐classification, and Karnofsky Performance Scale (KPS) ( p  < 0.05). For EBV +, HPV +, and EBV − /HPV − respectively, 3‐year overall survival (OS) was 89.9%, 69.8%, and 52.5% ( p  = 0.006). EBV − /HPV − status was significantly associated with worse OS but not freedom from progression (FFP) on univariate analysis, and did not remain a significant predictor of OS after adjusting for KPS, age, and group stage. Conclusions: EBV + NPC tumors were seen in younger, healthier patients than HPV + and EBV − tumors, and there were no cases of coinfection. The association of viral status with OS was insignificant after adjusting for KPS and age.